2015
DOI: 10.1093/annonc/mdv364
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance rituximab after autologous stem cell transplantation in patients with mantle cell lymphoma

Abstract: These data support that MR after ASCT for MCL confers a benefit in PFS and additionally suggest it may improve OS. General application of this strategy will require confirmation of benefit in prospective randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…In fact, patients who received maintenance rituximab had a 75% risk reduction in progression and 83% in death. Two other retrospective studies have also reported a benefit of rituximab maintenance in PFS and potentially OS when given post-ASCT (17, 18); nevertheless, our study has the largest number of patients. The only prospective randomized trial of post-ASCT maintenance rituximab is the phase 3 LyMa study, and the results were recently presented in ASH 2016.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, patients who received maintenance rituximab had a 75% risk reduction in progression and 83% in death. Two other retrospective studies have also reported a benefit of rituximab maintenance in PFS and potentially OS when given post-ASCT (17, 18); nevertheless, our study has the largest number of patients. The only prospective randomized trial of post-ASCT maintenance rituximab is the phase 3 LyMa study, and the results were recently presented in ASH 2016.…”
Section: Discussionmentioning
confidence: 78%
“…On multivariate analysis, MR therapy was associated with improved PFS (hazard ratio (HR) = 0.23; 95% confidence interval (CI) = 0.06-0.80), although no OS benefit was noted (HR = 0.61, 95% CI = 0.14-2.65). 31 Graf et al 32 similarly examined a cohort of patients which underwent ASCT followed by MR or observation. Although various rituximab administration schedules were evaluated, on multivariate analysis MR was associated with improved PFS (HR = 0.44; 95% CI = 0.24-0.80) along with OS (HR = 0.46; 95% CI = 0.23-0.93).…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…Although various rituximab administration schedules were evaluated, on multivariate analysis MR was associated with improved PFS (HR = 0.44; 95% CI = 0.24-0.80) along with OS (HR = 0.46; 95% CI = 0.23-0.93). 32 Recently, prospective studies have further investigated the role of maintenance therapy post ASCT in MCL. In the LYMA study, patients who achieved a PR or CR to high-dose chemotherapy followed by ASCT were randomized to either observation or MR (375 mg/m 2 every 2 months for 3 years).…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective and a few prospective studies have evaluated maintenance rituximab in MCL (Table 2). [84][85][86][87] Dietrich et al…”
Section: Mantle Cell Lymphoma (Mcl)mentioning
confidence: 99%